PENGARUH SPT MASA PPN, SURAT TAGIHAN PAJAK, JUMLAH PENGUSAHA KENA PAJAK, INFLASI DAN NILAI TUKAR RUPIAH TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI DI KPP PRATAMA KUDUS TAHUN 2017 - 2021 - Niamiyah, A'yunin; Budiman, Nita Andriyani; Hidayanti, Alfiyani Nur (Relevan : Jurnal Riset Akuntansi, 2024)
Taxes are government revenues which are generally used to finance all government activities. Taxes are also a measure of a country's economic success. Value Added Tax (VAT) is a tax obligation by every buyer for the added value of goods and/or services carried out by taxable entrepreneurs. This research aims to examine the influence of VAT SPT, tax invoices, number of taxable entrepreneurs, inflation, and the rupiah exchange rate on value added tax revenues. This research data comes from KPP Pratama Kudus for 2017-2021. The sampling technique used in this research was a saturated sampling technique of 47 samples. The data analysis method in this research is multiple linear regression analysis. The results of this research show that VAT SPT, tax bills, number of taxable entrepreneurs, inflation and the rupiah exchange rate have no effect on value added tax revenues.